Measurement and analysis system of the knee joint motion in gait evaluation for rehabilitation medicine - Neramitr Chirakanphaisarn (2018)
The purpose of this study is to create a device for measuring the knee joint motion during walking. Knee joint motion is one of the significant clinical parameters for assessing people who have difficulties in walking. Since commercial gait goniometers are very expensive and there are durability problems, the goal of this study was to construct a prototype of dynamic knee joint measuring equipment which is inexpensive, efficient, portable, and durable. The equipment can measure the angles of the knee joint motion in real time, and can record the measured values in an SD card immediately. Moreover, gait parameters can be analyzed. The subjects of the experiments are twenty normal people and twenty less disabled people at Ramathibodi hospital, Thailand. The results are compared with those measured by the commercial Ultra-Flex [8] for forty subjects while they walked at the comfortable speed. It was shown that both gave closely correlated graphs. Also, the experiments measured the knee joint motion using the prototype for the subjects before rehab, and after 3-month rehab. The results revealed that the walking signals of the subjects did improve. They also indicated that the knee joint angles of the subjects are close to the normal knee control after treatment. © 2014 IEEE.